Efficacy of dietary supplements targeting gut microbiota in the prevention and treatment of gestational diabetes mellitus - Wan, Jiayang; Ma, Jingmei (Frontiers in Microbiology, 2022)
Gestational diabetes mellitus (GDM) is a kind of metabolic disease occurring during gestation period, which often leads to adverse pregnancy outcomes and seriously harms the health of mothers and infants. The pathogenesis of GDM may be bound up with the abnormal gut microbiota composition in pregnant women. Previous studies have clarified that dietary supplements can regulate the gut microbiota to play a role. Therefore, using dietary supplements such as probiotics, prebiotics, and synbiotics to target the gut microbiota to regulate the disordered gut microbiota would become a potential method that benefits for preventing and treating GDM. This paper reviews a series of clinical trials in recent years, expounds on the clinical effects of dietary supplements such as probiotics on GDM, and discusses the intervention effects of dietary supplements on GDM related risk factors, including overweight, obesity, and type 2 diabetes mellitus (T2DM). In addition, the relationship of GDM and gut microbiota is also discussed, and the possible mechanisms of dietary supplements are summarized. This review will help to promote the further development of dietary supplements targeting gut microbiota and provide more knowledge support for clinical application in the prevention and treatment of various diseases.